THE INFLUENCE OF FINTECH DEVELOPMENT ON INTEREST IN NON-CASH TRANSACTIONS AMONG THE MEULABOH COMMUNITY IN WEST ACEH - Widasari; Muliza; Yoni Hendrawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The people of Meulaboh, West Aceh, continue to follow developments in information technology, as evidenced by the easy access to the internet in Meulaboh, West Aceh. Furthermore, a positive impact of technological developments in the financial sector is the ability to conduct cashless transactions through fintech. This study aims to examine the influence of fintech developments on the interest of the people of Meulaboh, West Aceh, in conducting cashless transactions. This study employed a quantitative research method, collecting data using questionnaires and analyzing data using simple regression tests. The results showed a significance value (Sig) of 0.000, lower than 0.05, and a t-value (t-count) of 24.113, greater than the t-table of 1.660. This concludes that fintech developments have a significant positive effect on the interest of the people of Meulaboh, West Aceh, in conducting cashless transactions.